Eye and Orbital Anatomy in Metopic Synostosis - Linda Gaillard, MD; Anna E. Puppels, BSc; Marjolein H.G. Dremmen, MD; Sjoukje E. Loudon, MD; Irene M.J. Mathijssen, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Metopic synostosis patients have a high prevalence of orthoptic anomalies, including hyperopia, astigmatism, and amblyopia. We hypothesized altered orbital anatomy contributes to suboptimal visual outcomes by adversely affecting eye anatomy and growth from early life onward. Therefore, we aimed to investigate eye and orbital anatomy in metopic synostosis. Methods:. We conducted a retrospective study in nonsyndromic metopic synostosis patients (n = 134, median age 0.43 years [IQR 0.45]) with nonsyndromic sagittal synostosis patients (n = 134, median age 0.27 years [IQR 0.23]) as controls. Primary analyses focused on eye dimensions (axial length, width, and globe height) and orbital dimensions, correcting for sex and age. Measurements were obtained from preoperative computed tomography scans. Results:. Axial length and width in metopic synostosis patients did not differ from sagittal synostosis patients, but globe height was significantly smaller (P = 0.0002). Lateral wall interorbital length, lateral orbital wall length, anterior medial interorbital length, and maximal medial interorbital length were significantly smaller, and anterior vertical orbital height and maximal vertical orbital height were significantly larger (P < 0.001). The central orbital axis and interorbital angle were significantly narrower, and medial-to-lateral orbital wall angle was wider (P < 0.001). Conclusions:. Metopic synostosis patients have more shallow, wider, and higher orbits. Eye dimensions are similar in sagittal synostosis patients, although globe height was smaller. Altered orbital and eye dimensions in metopic synostosis probably have a causal relation with an unknown order of development. How these dimensions relate to future orthoptic anomalies (eg, refractive error) needs further investigation.